Identifying the Problem of Banjarese Speaking Students in Learning English Pronunciation - Vivi Aulia (Journal of English Language Studies, 2018)
This article is a report of descriptive research aiming at identify the Banjarese speaking students in learning English pronunciation. This research is conducted towards the third semester students batch 2016 who have passed Pronunciation Practice I and II courses available at the English Department of STKIP PGRI Banjarmasin. Only the Banjarese speaking students are engaged as the subject of this research. The instruments used in this research are questionnaire and interview section. Both of the instruments are analyzed quantitatively by calculating the percentage of dominant answer given by students. The result of this research shows that most of Banjarese speaking students have problem relating to the interference of mother tongue while they are learning English pronunciation.  The difference of English, Indonesian, and Banjarese sound systems affect much on the success of students’ English pronunciation learning process. Having no prior knowledge of English pronunciation, having low motivation and other possible factors also take part in determining their learning result. Based on these results, the teacher’s or instructor’s pronounciation should consider allocating much attention to English pronunciation learning since it plays role in determining the success of oral communication. Keywords: problem, Banjarese speaking students, learning, and English pronunciation